Cellulose Based Nano-Scaffolds for Targeted Cancer Therapies: Current Status and Future Perspective - Li Y; Liu W; Wang Y; Lu S (International Journal of Nanomedicine)
Yanwei Li,1 Wei Liu,2 Yuanyuan Wang,3 Shan Lu1 1Department of General Practice and Family Medicine, The Second Hospital of Jilin University, Changchun, 130000, People’s Republic of China; 2Department of Radiology, The Second Hospital of Jilin University, Changchun, 130000, People’s Republic of China; 3Department of Radiotherapy, Central Hospital of Changchun City, Changchun, 130000, People’s Republic of ChinaCorrespondence: Shan Lu, Department of General Practice and Family Medicine, The Second Hospital of Jilin University, Changchun, 130000, People’s Republic of China, Email lushan@jlu.edu.cnAbstract: In the last few years, cellulose has garnered much interest for its application in drug delivery, especially in cancer therapy. It has special properties like biocompatibility, biodegradability, high porosity, and water permeability render it a good candidate for developing efficient carriers for anticancer agents. Cellulose based nanomaterials like cellulose nanofibers, bacterial cellulose, cellulose nanocrystals and microcrystalline cellulose as delivery vehicles for targeted drug delivery to cancer cells are reviewed. This review elaborates on the synthesis, functionalization, and application strategies of these nanocarriers, and shows how they facilitate to improve drug stability, bioavailability and targeted delivery to tumor sites. Their possibilities as a tool to overcome the limitations of conventional cancer therapeutics are also discussed. We also explore future directions for improving the efficacy of cellulose based carriers in cancer therapy.Keywords: cellulose – nanocarriers, cellulose scaffold, cellulose based cancer therapy, biomedical applications